MINAT SISWA DALAM PEMBELAJARAN DARING MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SMA NEGERI DI BOYOLALI - Enggar Jati Pratikto; Anugrah Nur Warthadi (Bajang Institute, 2021)
In education in schools, it must be done optimally to achieve the goals of learning itself, several factors affect the continuity of the smoothness of learning, especially in the current mass itself were at present in early 2020 there was a Covid-19 outbreak that occurred and befell in the world. around the world recently, and has an impact on education in schools and the implementation of distance learning and requires learning to be done online, what is meant by online learning or e-learning. The purpose of this study was to determine how much students' interest in online learning of PJOK subjects at SMA Negeri in Boyolali. The population and sample in this study were 483 state high school students in Boyolali, Central Java province with 74 students from SMAN 1 Boyolali, 138 students from SMAN 2 Boyolali, and 270 students from SMAN 3 Boyolali. Data analysis used descriptive analysis of frequency. The results of this study can be concluded that the student's interest in online learning in the PJOK subject at SMA Negeri in Boyolali is in the Enough category. This is evidenced by the results of the descriptive analysis of the frequency of the data obtained in the Enough category, the value range is 63,51% for SMA Negeri 1 Boyolali, 52.17% for SMA Negeri 2 Boyolali, and 53.70% for SMA Negeri 3 Boyolali.